A simple approach to optimum pool size for pooled SARS-CoV-2 testing. (November 2020) - Regen, Francesca; Eren, Neriman; Heuser, Isabella; Hellmann-Regen, Julian
Highlights: This study provides a guide towards making rational decisions on sample pooling/pool size. Sample pooling in SARS-CoV-2 RT-qPCR strikingly increases throughput. Pool size strikingly depends on target prevalence rates. While cost-savings from pooling – and optimum pool sizes – have been largely unclear, this study presents a simple-to-use formula to calculate the optimum pool size. The results are also applicable/generalizable to non-SARS-related testing strategies. Abstract: Systematic, large-scale testing of asymptomatic subjects is an important strategy in the management of the SARS-CoV-2 pandemic. In order to increase the capacity of laboratory-based molecular SARS-CoV-2 testing, it has been suggested to combine several samples and jointly measure them in a sample pool. While saving cost and labour at first sight, pooling efficiency depends on the pool size and the presently experienced prevalence of positive samples. Here we address the question of the optimum pool size at a given prevalence. We demonstrate the relation between analytical effort and pool size and delineate the effects of the target prevalence on the optimum pool size. Finally, we derive a simple-to-use formula and table that allow laboratories performing sample pooling to assess the optimum pool size at the currently experienced target prevalence rate.